Analysis of students' science process skills in human reflex practicum based on the guided inquiry learning - Mustaqimah, Nur; Usman, Nurul Fajryani; Nurhayati, Nurhayati; Nurbaya, Nurbaya (JPBIO (Jurnal Pendidikan Biologi), 2025)
Science process skills are essential abilities involving thinking, reasoning, and acting effectively to achieve scientific goals. While the Guided Inquiry Learning model has shown effectiveness in improving these skills, its application in the coordination system topic, particularly using human reflex practicum, remains under-researched. At SMAN 1 Tilango, Grade XI students learn the coordination system mainly through theoretical instruction, with limited practical activities. This reduces opportunities for students to develop science process skills such as observing, experimenting, and analyzing data. This study aimed to analyze learning implementation and students’ science process skills through a human reflex practicum using the Guided Inquiry Learning model. Conducted in October 2024 at SMAN 1 Tilango, the research involved 20 Grade XI students and used a quantitative descriptive method. Data were collected via observation sheets focused on learning implementation and science process skills. The findings showed that all learning stages were implemented effectively, and students actively engaged in scientific activities. The highest achievement was in observation skills, with an average score of 87%, classified as very good. The Guided Inquiry model offered meaningful learning experiences and improved students’ scientific understanding through direct involvement.